Recognition of asymptomatic hypercholanemia of pregnancy: Different clinical features, fetal outcomes and bile acids metabolism from intrahepatic cholestasis of pregnancy - He, Yifan; Zhang, Xiaoqing; Shao, Yong; Xu, Biao; Cui, Yue; Chen, Xiao; Chen, Hong; Luo, Can; Ding, Min (Biochimica et biophysica acta. Molecular basis of disease, 2022)
To explore the clinical features, fetal outcomes and serum bile acids (BAs) metabolism in asymptomatic hypercholanemia of pregnancy (AHP), as well as the comparison with those in intrahepatic cholestasis of pregnancy (ICP) and normal pregnancies. A study containing 676 pregnant women was performed to investigate the clinical informations, routine biochemical features and obstetric outcomes of AHP by the comparison with ICP and normal pregnancies. Within the study subjects, 203 pregnant women received prospective determination for 55 serum individual BAs based on a validated UPLC-QTOF-MS/MS method. The differences in clinical features and serum BAs metabolism among the three groups were then investigated. The risk of adverse fetal outcomes in AHP (28.3%) was significantly higher than that in normal pregnancies (8.9%, p < 0.001), but lower than that in ICP group (52.1%, p < 0.001). Multivariate statistics analysis indicated a distinctive serum BAs metabolic profiling among the three groups (PLS-DA, R2Y = 0.580, Q2 = 0.537). Levels of serum BAs especially for deoxycholic acid species were found remarkably elevated in AHP as compared to those in ICP. AHP group had distinguished clinical features and serum BAs metabolism as compared to ICP group and normal pregnancies. •AHP women suffered from hypercholanemia approximately five weeks earlier than ICP patients.•The risk of adverse fetal outcomes in AHP was significantly higher than that in normal pregnancies, but lower than that in ICP group.•AHP had distinctive serum BAs metabolic profiling from both ICP and normal pregnancies.•Levels of serum deoxycholic acid species were found remarkably elevated in AHP.